Is there evidence for changes in antibiotic resistance of microorganisms causing postcataract surgery endophthalmitis: a systematic review - Justine R Smith; Nieraj Jain; Maureen G Maguire; Leo A Kim; Christina J Flaxel; Steven Yeh; Stephen Jae Kim; Christina Y Weng (BMJ Open Ophthalmology)
Background/Aims To review the evidence for changes in antibiotic resistance patterns before and after cataract surgery since the advent of routine use of intracameral (IC) antibiotic prophylaxis and development of newer topical fluoroquinolones pre- and postcataract surgery.Methods Literature searches in the National Library of Medicine PubMed database were conducted between 2019 and 2021 and updated in 2024. There were no date restrictions, and the search was limited to high-quality studies published in English. The initial combined searches yielded 583 articles, and the search update in 2024 yielded 9 articles. Of these 592 articles, 26 presented original research that met specified inclusion criteria. Reviewed studies were rated based on the Oxford Centre for Evidence-Based Medicine grading system. Because results from the various studies are not directly comparable due to the use of different antibiotics, different methods, different study populations and different outcomes, formal analyses for heterogeneity of results and publication bias were not performed.Results There were no studies that presented definitive level I evidence for increased bacterial resistance to IC or oral antibiotics prior to or during routine cataract surgery. There were no studies that provided level I evidence for increased bacterial resistance to topical administration of antibiotics. One study showed level III evidence for potential antibiotic resistance when the antibiotic was administered for greater than 1 month, and four level III studies showed a possible trend towards increased moxifloxacin and ciprofloxacin resistance.Conclusions There is little evidence of increased bacterial resistance following the use of newer fluoroquinolone antibiotic prophylaxis prior to cataract surgery or the routine use of IC antibiotic prophylaxis during cataract surgery. Our work is limited by the lack of high-level evidence on antibiotic resistance. Many studies reviewed are not randomised controlled trial (RCTs), introducing biases and confounding factors. Small sample sizes further reduce reliability, and uncontrolled variables, such as regional prescribing patterns, may lead to misleading results. While lower level evidence offers some insights, cautious interpretation is advised until more rigorous RCTs are conducted.